2021
DOI: 10.3389/fphys.2021.666964
|View full text |Cite
|
Sign up to set email alerts
|

Potential Utility of Electrical Impedance Myography in Evaluating Age-Related Skeletal Muscle Function Deficits

Abstract: Skeletal muscle function deficits associated with advancing age are due to several physiological and morphological changes including loss of muscle size and quality (conceptualized as a reduction in the intrinsic force-generating capacity of a muscle when adjusted for muscle size). Several factors can contribute to loss of muscle quality, including denervation, excitation-contraction uncoupling, increased fibrosis, and myosteatosis (excessive levels of inter- and intramuscular adipose tissue and intramyocellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 97 publications
0
21
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first report to evaluate EIM for inflammatory skeletal muscle dysfunction after surgery. Previous studies have shown that the impedance parameters measured by EIM are associated with age-related changes in skeletal muscle and neuromuscular diseases [ 2 ]. In this case, acute changes in skeletal muscle function caused by inflammatory reactions after thoracotomy were serially evaluated using ultrasonography and EIM to determine the efficacy of EIM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first report to evaluate EIM for inflammatory skeletal muscle dysfunction after surgery. Previous studies have shown that the impedance parameters measured by EIM are associated with age-related changes in skeletal muscle and neuromuscular diseases [ 2 ]. In this case, acute changes in skeletal muscle function caused by inflammatory reactions after thoracotomy were serially evaluated using ultrasonography and EIM to determine the efficacy of EIM.…”
Section: Discussionmentioning
confidence: 99%
“…EIM has been reported to be effective in aging and sarcopenia-induced changes in skeletal muscle function [ 2 ]. Because EIM is sensitive to minor morphological changes, such as cell density and size in tissues, it is useful not only for age-related changes but also for disease-genic changes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is gap in the literature in assessing if large or small sensors are sufficiently reliable for clinical application, or if their reliability may differ when measuring a single muscle group by different rates at different time. A recent review by Clark et al argued that there continues to be a lack of evidence to support the clinical application of EIM in assessing skeletal muscle function [ 22 ]. These issues must be addressed to facilitate clinical application of EIM.…”
Section: Introductionmentioning
confidence: 99%